Does competitive environment moderate the market orientation : performance relationship in the Singapore context? - Tay, Patrick Nam Koon (2014)
Over the past thirty years, Singapore has progressed from a low-costbased economy to a high-valued added one. As such, there is a need for organisations in Singapore to be market oriented so as to maintain their competitive edge. Recent studies have shown evidence of a positive relationship between market orientation and performance. It was suggested in the literah1re that competitive environment could moderate this relationship. The authors investigate how competitive environment affects the strength of the market orientation-performance relationship. The results provided very limited support for a moderator role for competitive environment on the market orientation-performance relationship. The benefits of a market orientation are long term though environment conditions are often transient, and thus being market oriented is cost effective in spite of any possible short term moderating effects of the environment.